Hippocampal Neurodegenerative Pathology in Post-stroke Dementia Compared to Other Dementias and Aging Controls - Akinyemi, Rufus O.; Allan, Louise M.; Oakley, Arthur; Kalaria, Rajesh N. (Frontiers in Neuroscience, 2017)
Neuroimaging evidence from older stroke survivors in Nigeria and Northeast England showed medial temporal lobe atrophy (MTLA) to be independently associated with post-stroke cognitive impairment and dementia. Given the hypothesis ascribing MTLA to neurodegenerative processes, we assessed Alzheimer pathology in the hippocampal formation and entorhinal cortex of autopsied brains from of post-stroke demented and non - demented subjects in comparison with controls and other dementias. We quantified markers of amyloid β (total Aβ, Aβ - 40, Aβ - 42, and soluble Aβ) and hyperphosphorylated tau in the hippocampal formation and entorhinal cortex of 94 subjects consisting of normal controls (n =12), vascular dementia, VaD (17), post - stroke demented, PSD (n =15), and post - stroke non - demented, PSND (n = 23), Alzheimer’s disease, AD (n = 14), and mixed AD and vascular dementia, AD_VAD (n = 13) using immunohistochemical techniques. We found differential expression of amyloid and tau across the disease groups, and across hippocampal sub-regions. Among amyloid markers, the pattern of Aβ - 42 immunoreactivity was similar to that of total Aβ. Tau immunoreactivity showed highest expression in the AD and AD-VaD mixed groups, which was higher than in control post-stroke and VaD groups (p < 0.05). APOE Ɛ4 allele positivity was associated with higher expression of amyloid and tau pathology in the subiculum and entorhinal cortex of post-stroke cases (p < 0.05). Comparison between PSND and PSD revealed higher total Aβ immunoreactivity in PSND compared to PSD in the CA1, subiculum and entorhinal cortex (p < 0.05) but no differences between PSND and PSD in Aβ - 42, Aβ - 40, soluble Aβ or tau immunoreactivities (p > 0.05). Correlation of MMSE and CAMCOG scores with AD pathological measures showed lack of correlation with amyloid species although tau immunoreactivity demonstrated correlation with memory scores (p < 0.05). Our findings suggest hippocampal AD pathology does not necessarily differ between demented and non-demented post-stroke subjects. The dissociation of cognitive performance with hippocampal AD pathological burden suggests more dominant roles for non – Alzheimer neurodegenerative and / or other non - neurodegenerative substrates for dementia following stroke.